PEMANFAATAN WEBSITE INTERAKTIF DENGAN DUKUNGAN AI SEBAGAI MEDIA PEMBELAJARAN DASAR-DASAR CODING BAGI SISWA SMPN 3 KOTA TANGERANG SELATAN - Dede Supiyan; Deswita Amelia Anjeli; Maria Raflesia Heskey Naraha; Muhammad Dava Rayhan; Pedro Yong; Ramzy albar; Royhan Arfah Hakim Harahap; Salwa Rosianita; Satrio Rafli Sangaji; Sutikno Aji (Abdi Jurnal Publikasi, 2026)
Learning basic coding is an important skill in today's digital world. It is especially relevant for middle school students who need to develop computational thinking early on. This study aims to create and test the effectiveness of an interactive website with artificial intelligence (AI) as a learning tool for coding for students at SMPN 3 Tangerang Selatan. The website offers interactive modules such as step-by-step tutorials, practical exercises, and AI features that provide automatic feedback, error correction, and personalized learning recommendations based on students' progress. The research uses a software development approach with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), involving 50 students from SMPN 3 as test subjects. Data was collected through surveys, coding understanding tests, and observations of student participation before and after using the website. The results showed a significant improvement in understanding basic coding concepts such as variables, loops, and conditions, by 35%. Additionally, student engagement increased by 40% compared to traditional learning methods. The AI features were found to be effective in reducing individual learning difficulties, with student satisfaction reaching 85%. The conclusion of this study emphasizes that an AI-based interactive website can be an innovative choice to improve the effectiveness of coding learning at the middle school level. This study encourages further development for wider implementation and contributes to the field of educational technology, especially in Indonesia.